Effects of a Self-Esteem Enhancement Program on Happiness and Depression in Pregnant Adolescents: A Randomized Controlled Trial - Chokrak, Suppalack; Chunuan, Sopen; Phumdoung, Sasitorn (Pacific Rim International Journal of Nursing Research, 2025)
Pregnant women commonly experience feelings of unhappiness and depression during pregnancy, and depression has a negative impact on pregnant adolescents. This randomized controlled trial aimed to examine the effects of a Self-Esteem Enhancement Program on feelings of happiness and depression in pregnant adolescents. The sample consisted of pregnant adolescents who attended the antenatal clinic of a community hospital in southern Thailand from January to May 2024. The sample was randomly assigned to an experimental group and a control group using minimized randomization controlling for potential confounders. The experimental group (n = 21) received the program, while the control group (n = 25) received only usual care. Data collection was conducted using a Personal Information Questionnaire, the Self-esteem Questionnaire the Center for Epidemiologic Studies Depression Scale (CESD-10), and the Happiness in Pregnancy Questionnaire (HPQ). Data were analyzed using descriptive statistics, paired t-test, independent t-test, Wilcoxon signed ranks test, and Mann-Whitney U test. The results showed that pregnant adolescents in the experimental group exhibited significantly higher mean scores for happiness and lower depression scores after completing the self-esteem enhancement program compared to their scores before the program. Additionally, a comparison between the two groups following the intervention showed that the experimental group had significantly higher happiness and lower depression than those in the control group. These findings suggest that the program effectively increased happiness and decreased depression among pregnant adolescents. Therefore, nurses and midwives should consider this program as a valuable guide for the care of pregnant adolescents. However, wide testing of this program is needed before integration into regular practice.